Evaluation of Norovirus Reduction in Environmentally Contaminated Pacific Oysters During Laboratory Controlled and Commercial Depuration - Agnieszka Rupnik; William Doré; Leon Devilly; James Fahy; Amy Fitzpatrick; Wiebke Schmidt; Kevin Hunt; Francis Butler; Sinéad Keaveney (Food and Environmental Virology, 2021)
Norovirus contamination of oysters is the lead cause of non-bacterial gastroenteritis and a significant food safety concern for the oyster industry. Here, norovirus reduction from Pacific oysters ( Crassostrea gigas), contaminated in the marine environment, was studied in laboratory depuration trials and in two commercial settings. Norovirus concentrations were measured in oyster digestive tissue before, during and post-depuration using the ISO 15216-1 quantitative real-time RT-PCR method. Results of the laboratory-based studies demonstrate that statistically significant reductions of up to 74% of the initial norovirus GII concentration was achieved after 3 days at 17–21 °C and after 4 days at 11–15 °C, compared to 44% reduction at 7–9 °C. In many trials norovirus GII concentrations were reduced to levels below 100 genome copies per gram (gcg −1 ; limit of quantitation; LOQ). Virus reduction was also assessed in commercial depuration systems, routinely used by two Irish oyster producers. Up to 68% reduction was recorded for norovirus GI and up to 90% for norovirus GII reducing the geometric mean virus concentration close to or below the LOQ. In both commercial settings there was a significant difference between the levels of reduction of norovirus GI compared to GII ( p < 0.05). Additionally, the ability to reduce the norovirus concentration in oysters to < LOQ differed when contaminated with concentrations below and above 1000 gcg −1 . These results indicate that depuration, carried out at elevated (> 11 °C) water temperatures for at least 3 days, can reduce the concentration of norovirus in oysters and therefore consumer exposure providing a practical risk management tool for the shellfish industry.

The Impact of Winter Relocation and Depuration on Norovirus Concentrations in Pacific Oysters Harvested from a Commercial Production Site - Agnieszka Rupnik; Sinéad Keaveney; Leon Devilly; Francis Butler; William Doré (Food and Environmental Virology, 2018)